Cesarean Section or Vaginal Delivery to Prevent Possible Vertical Transmission From a Pregnant Mother Confirmed With COVID-19 to a Neonate: A Systematic Review - Cai, Jianghui; Tang, Mi; Gao, Yu; Zhang, Hongxi; Yang, Yanfeng; Zhang, Dan; Wang, Han; Liang, Hua; Zhang, Rui; Wu, Bo (Frontiers in Medicine, 2021)
Background: The impact of delivery mode on the infection rates of Coronavirus disease 2019 (COVID-19) in the newborn remains unknown. We aimed to summarize the existing literature on COVID-19 infection during pregnancy to evaluate which mode of delivery is better for preventing possible vertical transmission from a pregnant mother confirmed with COVID-19 to a neonate. Methods: We performed a comprehensive literature search of PubMed, Embase, Cochrane Library, Web of Science, Google Scholar, and the Chinese Biomedical Literature database (CBM) from 31 December 2019 to 18 June 2020. We applied no language restrictions. We screened abstracts for relevance, extracted data, and assessed the risk of bias in duplicate. We rated the certainty of evidence using the GRADE approach. The primary outcome was severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test positivity in neonates born to mothers with confirmed COVID-19 following different delivery modes. Secondary outcomes were neonatal deaths and maternal deaths. This study is registered with PROSPERO, CRD42020194049. Results: Sixty-eight observational studies meeting inclusion criteria were included in the current study, with no randomized controlled trials. In total, information on the mode of delivery, detailed neonatal outcomes, and SARS-CoV-2 status were available for 1,019 pregnant women and 1,035 neonates. Six hundred and eighteen (59.71%) neonates were born through cesarean section and 417(40.29%) through vaginal delivery. Probable congenital SARS-CoV-2 infections were reported in 34/1,035 (3.29%) neonates. Of babies born vaginally, 9/417 (2.16%) were tested positive compared with 25/618 (4.05%) born by cesarean. Of babies born vaginally, 0/417 (0.00%) neonatal deaths were reported compared with 6/618 (0.97%) born by cesarean. Of women who delivered vaginally, 1/416 (0.24%) maternal deaths were reported compared with 11/603 (1.82%) delivered by cesarean. Two women died before delivery. Sensitivity analyses and subgroup analyses showed similar findings. Conclusions: The rate of neonatal COVID-19 infection, neonatal deaths, and maternal deaths are no greater when the mother gave birth through vaginal delivery. Based on the evidence available, there is no sufficient evidence supporting that the cesarean section is better than vaginal delivery in preventing possible vertical transmission from a pregnant mother confirmed with COVID-19 to a neonate. The mode of birth should be individualized and based on disease severity and obstetric indications. Additional good-quality studies with comprehensive serial tests from multiple specimens are urgently needed. Study registration: PROSPERO CRD42020194049.